Loss of temporal retinal nerve fibers in Parkinson disease: a mitochondrial pattern?. Issue 1 (21st March 2012) - La Morgia, C.; Barboni, P.; Rizzo, G.; Carbonelli, M.; Savini, G.; Scaglione, C.; Capellari, S.; Bonazza, S.; Giannoccaro, M. P.; Calandra‐Buonaura, G.; Liguori, R.; Cortelli, P.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose: Optic nerve involvement is frequent in mitochondrial disease, and retinal abnormalities are described in Parkinson's disease (PD). Methods: We evaluated retinal nerve fiber layer (RNFL) thickness by optical coherence tomography in 43 patients with PD and in 86 age‐matched controls. We considered separately the eyes ipsilateral and contralateral to the most affected body side in patients with PD. ancova analysis, Pearson test, and multiple regression analysis were used (P < 0.05). Results: Patients with PD showed significantly thinner temporal RNFL thickness compared to controls (P = 0.004), more evident in the eye contralateral to the most affected body side. Average RNFL thickness significantly correlated with age in both controls and patients with PD (P‐values ranging from 0.001 to 0.019), whereas in patients with PD RNFL thickness did not correlate with clinical variables. Conclusions: Our study reveals a loss of retinal nerve fibers in the temporal quadrant in PD, which is typically susceptible in mitochondrial optic neuropathies.